Climate change, gender, youth and nutrition situation analysis - Ethiopia - Pinto, Alessandro de; Bryan, Elizabeth; Aberman, Noora-Lisa (2019)
Provides a situational analysis for climate change, gender, youth, and nutrition in Ethiopia.